Rumus kln + X + setia + kln + Y ->Z dalam memahami penggunaan leksis setia berdasarkan perspektif linguistik kognitif (Jurnal Bahasa, 2022)
This study attempts to devise a formula with which to understand the lexical use of the word setia (loyalty; setia is categorised under the semantic category of values and exhibits complexity of meaning) in real sentences produced by language users. The investigation is based on a corpus of newspapers, books and magazines and shows that the giver (X) and the receiver (Y) of setia do not necessarily need to be people. In fact, they can be concrete objects or abstract concepts that have been personified. In addition, between X and Y there exist grammatical collocations (gc - daripada and kepada). This situation leads to the possibility of creating the formula gc + X + setia + gc + Y-> Z. However, there are times this formula may not reflect actual language use because people may manipulate their vocabulary usage beyond the parameters of the formula. Regardless of this, and more importantly, this attempt to come up with a “user-based formula” from a cognitive linguistic perspective enables scientific and academic debate.